One-stage hybrid aortic repair using the frozen elephant trunk in acute DeBakey type I aortic dissection - Goebel, Nora; Nagib, Ragi; Salehi-Gilani, Schahriar; Ahad, Samir; Albert, Marc; Ursulescu, Adrian; Franke, Ulrich F. W. (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: The extent of emergent surgery for acute DeBakey type I aortic dissection is discussed controversial. The frozen elephant trunk (FET) technique in addition to ascending and arch repair promotes aortic remodelling in the descending aorta and thus may provide superior long-term results in terms of less secondary re-interventions and reduced mortality linked to the downstream aorta. Methods: Between October 2009 and December 2016, a total of 72 patients underwent emergent hybrid aortic repair using the FET for acute DeBakey type I aortic dissection at our centre. Data were analysed from our prospectively collected database and clinical and imaging mid-term follow-up was obtained. Results: Implant success was 98.6% with an overall 30-day-mortality of 15.3%. New postoperative stroke was seen in 2.8%, new spinal cord injury in 4.2%. In follow-up (mean 37.8±21.2 months) cumulative survival was 75.0% with freedom from distal reintervention in 96.7% and aortic remodelling rate in the descending aorta in 96.5%. Conclusions: Hybrid aortic repair using the FET in acute DeBakey type I aortic dissection does not elevate the perioperative risk of mortality and provides excellent aortic remodelling with low distal re-intervention rate in mid-term follow-up.